2006
DOI: 10.1016/j.taap.2005.06.003
|View full text |Cite
|
Sign up to set email alerts
|

Pyrethroid pesticide-induced alterations in dopamine transporter function

Abstract: Parkinson's disease (PD) is a progressive neurodegenerative disease affecting the nigrostriatal dopaminergic pathway. Several epidemiological studies have demonstrated an association between pesticide exposure and the incidence of PD. Studies from our laboratory and others have demonstrated that certain pesticides increase levels of the dopamine transporter (DAT), an integral component of dopaminergic neurotransmission and a gateway for dopaminergic neurotoxins. Here, we report that repeated exposure (3 inject… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
63
0
1

Year Published

2007
2007
2021
2021

Publication Types

Select...
8
2

Relationship

2
8

Authors

Journals

citations
Cited by 104 publications
(65 citation statements)
references
References 51 publications
1
63
0
1
Order By: Relevance
“…However, the effect of long-term exposure to low-level PYRs on human health has been little characterized. A number of epidemiological studies have suggested the relationship between Parkinson's disease (PD) and environmental exposure to pesticides (Tanner and Langston, 1990;Gorell et al, 1998;Priyadarshi et al, 2001); a recent experimental study corroborated the possible underlying mechanism that in vivo exposure to PYRs, deltamethrin and permethrin, increases dopamine transporter and transporter-mediated dopamine uptake in the striatal synaptosome (Elwan et al, 2006). Also revealed by a recent study was the estrogenicity of PYR metabolites (McCarthy et al, 2006).…”
Section: Introductionmentioning
confidence: 94%
“…However, the effect of long-term exposure to low-level PYRs on human health has been little characterized. A number of epidemiological studies have suggested the relationship between Parkinson's disease (PD) and environmental exposure to pesticides (Tanner and Langston, 1990;Gorell et al, 1998;Priyadarshi et al, 2001); a recent experimental study corroborated the possible underlying mechanism that in vivo exposure to PYRs, deltamethrin and permethrin, increases dopamine transporter and transporter-mediated dopamine uptake in the striatal synaptosome (Elwan et al, 2006). Also revealed by a recent study was the estrogenicity of PYR metabolites (McCarthy et al, 2006).…”
Section: Introductionmentioning
confidence: 94%
“…Pyrethroid intoxication has long been known to cause neurological symptoms including salivation, tremor, choreoathetosis or coma, depending on the specific exposure. Several studies have reported the ability of pyrethroids, such as permethrin and deltamethrin, to increase DAT-mediated 3 H-dopamine uptake or cause neurotransmitter release [70,71]. Given the importance of DAT function to the dopamine neuron [72], this is an area of research that deserves more attention.…”
Section: Pyrethrins/pyrethroidsmentioning
confidence: 99%
“…Uptake rates were calculated as specific uptake (total uptake minus non-specific uptake), with non-specific uptake defined by the inclusion of 10 μM nomifensine. Following determination of synaptosomal protein concentration (Bradford, 1976), uptake rates were calculated as pmol/ mg/min protein and expressed as percentage of control values.Determination of 3 H-WIN 35,428 binding to DAT was performed as previously described (Elwan et al, 2006). Binding studies were conducted with crude synaptosomes and a single concentration (10nM) of 3 H-WIN 35,428 in 25 mM sodium phosphate buffer (125 mM NaCl, 5 mM KCl; pH 7.4) for one hour at 4°C in 96-well plates.…”
mentioning
confidence: 99%